Root Tensile Resistance of Selected Pennisetum species and shear strength of Root-Permeated Soil - Afaff Emhemed Ettbeb; Zulfahmi Ali Rahman; Wan Mohd Razi Idris; Jumaat Adam; Md Saffie Abd. Rahim; S. N. Ahmad Tarmidzi; Tukimat Lihan (Hindawi, 2020)
It is widely recognized that vegetation plays a significant role in contrasting slope instability through the root reinforcement. The main objectives of this paper are to evaluate the root tensile of selected Pennisetum species, namely, P. pedicellatum (PPd) and P. polystachion (PPl), and to determine the soil shear strength of root-permeated soil from these species. The selected species were initially planted in the polybags using the hydroseeding technique. A mineral fertilizer of NPK ratio 10 : 8 : 10 was adopted in the hydroseeding mixture. Routine watering program was applied twice a day throughout growth observation for six months. Four replications were prepared for each species including a set of control polybags, which contained only soil for reference and comparison. The results of root tensile tests revealed the significant relationships between root diameter and tensile force. In comparison, the PPl was still indicated by higher values of root tensile force than PPd. The presence of roots clearly has contributed to the shear stress of root-permeated soils. The root density based on root biomass measurement attributed to the higher value of peak shear stress as achieved by PPl than PPd. The combined effects of root tensile and the soil shear strengths of this selected species can be used as biological materials in slope protection against erosion.